In vitro culture of human-infecting Encephalitozoon spp. for genome sequencing with minimal host contaminant - Anne Caroline Mascarenhas dos Santos; Pingdong Liang; Oscar X. Juárez; Jean-François Pombert; Karina Tuz (PLoS ONE, 2026)
Microsporidia are obligate intracellular parasites infecting a wide range of hosts, including humans. They can cause severe infectious diseases if left untreated, particularly in immunocompromised individuals. The propagation of the human-infecting microsporidian species in vitro is essential for generating sufficient material for genomics studies, yet existing protocols often lack detail, accessibility, or strategies to minimize host DNA contamination. Here, we present an optimized, reproducible protocol for culturing Encephalitozoon spp. in human foreskin fibroblasts (HFF-1), designed to produce high-yield and high-quality genomic DNA with minimal host DNA for downstream sequencing experiments. In one month, our method yielded approximately one billion spores, which were purified using mechanical disruption, filtration, detergent treatment, and DNase I treatment to remove free host DNA. The reduction of host DNA was validated through PCR, and next-generation sequencing – with Illumina, PacBio and Oxford Nanopore – revealing that 83–97% of the reads mapped to microsporidian genomes. This protocol enabled the generation of the first telomere-to-telomere assemblies for E. cuniculi , E. hellem, and E. intestinalis . Our workflow provides a robust framework for producing microsporidian genomic material suitable for advanced genomics applications, with potential adaptability to other intracellular pathogens.